Congenital Heart Defects Recent Advances - Syamasundar Rao, P. (IntechOpen, 2022)
Over the last 50 years, there have been remarkable developments in the diagnosis and treatment of congenital heart defects. This book addresses some of these developments, including the role of echocardiography in improving the prognosis of fetal heart defects, benefits of new echo techniques, cardiac screening of participants in sports, management of premature babies with patent ductus arteriosus, and advantages of stenting the right ventricular outflow tract. It also discusses several types of heart defects, including ventricular septal defect, atrioventricular septal defect, hypoplastic left heart syndrome, and Ebstein's anomaly of the tricuspid valve. Finally, the book discusses the treatment of congenital aortic valve disease and issues related to managing congenital heart disease in developing countries.